2018
DOI: 10.1002/jcb.27575
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin as an effective anticancer natural product: Spotlight on TRAIL, WNT/β‐catenin, JAK‐STAT pathways, and microRNAs

Abstract: Wealth of information gleaned from decades of high‐impact research work; scientists have disentangled the complicated web of versatile regulators that underlie cancer development and progression. Use of structural biology approaches and functional genomics have helped us to gain new insights into complex nature of cancer, and it is now clear that genetic/epigenetic mutations, overexpression of oncogenes, inactivation of tumor suppressors, loss of apoptosis, and versatility of protein binding partners have cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 46 publications
(115 reference statements)
1
37
0
Order By: Relevance
“…These doses correspond to those of CuNPs that can be ingested and that have been applied in previous animal experiments, both in vivo and in vitro [ 20 , 58 , 59 , 60 , 61 ]. The dose of the plant additives was selected on the basis of the doses used in the corresponding previous in vitro experiments [ 41 , 43 , 45 , 49 , 50 ]. These substances were dissolved in the culture medium just before their addition to the cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These doses correspond to those of CuNPs that can be ingested and that have been applied in previous animal experiments, both in vivo and in vitro [ 20 , 58 , 59 , 60 , 61 ]. The dose of the plant additives was selected on the basis of the doses used in the corresponding previous in vitro experiments [ 41 , 43 , 45 , 49 , 50 ]. These substances were dissolved in the culture medium just before their addition to the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Rutin was able to prevent also the symptoms of polycystic ovarian syndrome [ 47 ]. Another flavonoid-type phytoestrogen, apigenin, is able to suppress proliferation and viability, and to promote oxidative stress and apoptosis in non-ovarian [ 48 , 49 ] and ovarian [ 50 ] cancer cells. It can restore ovarian folliculogenesis, ovulation, and steroidogenesis during polycystic ovarian syndrome [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of these studies showed that in cancers with overexpression of miR-423-5p the apoptosis mechanisms induced by Apigenin was severely destroyed. miR-423-5p was reported to be frequently overexpressed in glioma stem cells, and signi cantly increased apigenin related apoptosis developed in the use of miR-423-5p inhibitors [26]. The overexpression of miR-423-5p was reported to increase the colonisation, mobility, migration, and invasion capacity of LAD cells (Human mast cell greed LAD1, and LAD2) [27], however, in rat studies was reported to induce the tumorigenesis, and brain metastasis [28].…”
Section: Discussionmentioning
confidence: 99%
“…105 For example, apigenin from Epimedium koreanum Nakai, emodin from Rheum palmatum L, quercetin from Hypericun ascyron L and curcumin from Curcuma louga L are all reported to modulate various chronic diseases within safe dose range. [106][107][108][109] Here in this article, we systematically review the existing literature concerning coptisine's diverse beneficial properties, and this continues to support the recommendation that coptisine can be applied to the treatment for cancer, inflammation, CVDs and metabolic disorders.…”
Section: Future Pros Pec Tsmentioning
confidence: 98%